Getting started with Arduino - Banzi, Massimo, ....-; Shiloh, Michael, ....- (Sebastopol : Maker Media, 2015)
Learn about "interaction design and physical computing, the Arduino board and its software environment, basics of electricity and electronics, prototyping on a solderless breadboard, drasing a schematic diagram, talking to a computer--and the cloud--from arduino, building a custom plant-watering system," and more.--Back cover.
The Arduino way -- The Arduino platform -- Really getting started with Arduino -- Advanced input and output -- The Arduino Leonardo -- Talking to the cloud -- Automatic garden-irrigation system -- Troubleshooting.
Previous edition: 2011.
Includes index.
Keywords: Arduino (Programmable controller).; Electronics -- Data processing; Prototypes, Engineering; Open source software